2015
DOI: 10.1177/0030222815574689
|View full text |Cite
|
Sign up to set email alerts
|

The Religion of “I Don’t Know”

Abstract: The goal of this pilot study was to identify naturally occurring, spiritually relevant conversations and elucidate challenges for nurses in home hospice. We examined naturalistic communication data collected during nurse hospice visits with cancer patients and their family caregivers. Using deductive content analysis, guided by Consensus Conference spiritual categories and definition, categorical themes were identified. Thirty-three visits to seven families were recorded by five nurses. Although most spiritual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…than patients yet were more likely to change the subject (Ellington et al, 2015). Conversely, Wittenberg et al (2017) found that patients or families were most likely to initiate spiritual discussions.…”
Section: Detecting Spiritual Needs: Key Communication Skills and Techmentioning
confidence: 95%
See 4 more Smart Citations
“…than patients yet were more likely to change the subject (Ellington et al, 2015). Conversely, Wittenberg et al (2017) found that patients or families were most likely to initiate spiritual discussions.…”
Section: Detecting Spiritual Needs: Key Communication Skills and Techmentioning
confidence: 95%
“…Carroll (2001) differentiated between nurses who have a belief in God/universe and those who are agnostic/atheists. Ellington et al (2015) provided the religious/ spiritual identity of the patient families as Christian or Mormon. One study (Minton, Isaacson, Varilek, Stadick, & O-Connell-Persaud, S., 2018) identified the researchers' religious heritage as Christian and one study (Pittroff, 2013) identified the researcher as a lay minister in a Christian denomination.…”
Section: Ta B L E 1 Search Termsmentioning
confidence: 99%
See 3 more Smart Citations